Tiredness, depression, and sleep disorders in frontline healthcare workers during COVID-19 pandemic in Vietnam: A field hospital study - Duong-Quy, Sy; Tran-Duc, Si; Hoang-Chau-Bao, Dinh; Bui-Diem, Khue; Vu-Tran-Thien, Quan; Nguyen-Nhu, Vinh (Frontiers in Psychiatry, 2022)
Background The COVID-19 outbreak witnessed in the autumn of 2021 led to unprecedented changes in healthcare systems in some emerging countries. Many field-hospitals, temporary sites of care for COVID-19 patients, were built around the country and followed by the healthcare workers who were mobilized. This study aimed to measure sleep disorders, depression, and fatigue in volunteers working at field hospitals during the COVID-19 outbreak. Methods This was a cross-sectional study. The self-report questionnaire was used for each study subject. Sleep characters, including STOP's elements were questioned. Healthcare workers' burnout was detected by using Pichot's questionnaire. Results One hundred front-line healthcare workers (FHWs), predominantly last year and graduated medical students, were included in the study (86% female subjects). The mean sleep-time of FHWs before, while working, and during the isolation period after working at COVID-19 field hospitals were: 7.78 ± 1.48, 5.71 ± 1.40, and 8.78 ± 2.31 h per day, respectively. Burnout was not a crucial issue for these volunteer subjects. The mean scores of Pichot's Fatigue Scale and Pichot's Depression Scale, measured after 4 weeks working at field hospitals, were 4.18 ± 5.42 and 2.54 ± 3.36, respectively. Thirteen participants were suspected of depression. The fatigue scores decreased significantly in the group who claimed short sleep latency. The factor that increased the depression score was “anxious feeling” (p = 0.001). Other significant factors were “short sleep latency,” “observed sleep apnea,” “tiredness, daily sleepiness” and “snoring.” Conclusion Appropriate work schedule, better sleep conditions, and mental health support could be helpful for FHWs. The mandatory 2 weeks of isolation after working in field hospitals provided opportunity for FHWs' recovery.